2009
DOI: 10.1111/j.1526-4637.2008.00511.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Comprehensive E-Learning Resource in Pain Management

Abstract: The VCU Chronic Nonmalignant Pain Management curriculum is an e-learning resource that has the potential to fill a significant training void. Design and content changes have been made as a result of initial evaluation data. Data from ongoing evaluation will allow curricular refinement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 36 publications
0
31
0
2
Order By: Relevance
“…13 Briefly, VCU Pain Management is an innovative case-based curriculum that covers pain assessment and treatment, fibromyalgia, neuropathic pain, prescription drug misuse, and legal aspects of controlled substance prescribing. In line with national trends in medical education, PPM was absent from the pain management curriculum.…”
Section: Module Developmentmentioning
confidence: 99%
“…13 Briefly, VCU Pain Management is an innovative case-based curriculum that covers pain assessment and treatment, fibromyalgia, neuropathic pain, prescription drug misuse, and legal aspects of controlled substance prescribing. In line with national trends in medical education, PPM was absent from the pain management curriculum.…”
Section: Module Developmentmentioning
confidence: 99%
“…The need for training in pain assessment is well documented in human medicine (Yanni et al. ; Murinson et al. ; Keefe & Wharrad ).…”
Section: Introductionmentioning
confidence: 99%
“…25 Recently proposed enriched medical student pain curricula are often limited to a short interval, concentrated intersession or web-based content. 22,29,36 Mezei and Murinson 21 reported an extensive survey of all pain content taught in U.S. medical schools and found a median of just 7 sessions with a range of 1 to 28 and found that only 4% of medical schools have integrated pain material within case-based clinical teaching settings. The British Pain Society in 2009 and Briggs et al 7 have reported 13 hours of median pain curriculum in UK medical school curricula.…”
mentioning
confidence: 99%